Rare presentations of ordinary lipomas of the head and neck: a review. - Som, P M; Scherl, M P; Rao, V M; Biller, H F (American Journal of Neuroradiology, 1986)
The ordinary lipoma is the most common neoplasm of mesenchymal origin. Only 13% of them arise in the head and neck region and most of these occur subcutaneously in the posterior neck. Rarely, they can develop in the anterior neck, infratemporal fossa, and in or around the oral cavity, pharynx, larynx, and parotid gland. Clinically, they can be confused with other benign lesions; however, CT allows a specific diagnosis to be made in virtually all cases. This article reviews the CT appearance and differential diagnoses of lipomas in these rare locations and discusses the rare infiltrating lipoma and the relationship between parotid lipomatosis and sialosis.